Development and Survivability of The Free-Living Stage Larvae of Equine Strongyles in Different Environments and Soil Types - Idzana Ab Malek; Fuziaton Baharudin; Tan Li Peng; Jasni Sabri (Tropical Life Sciences Research, 2025)
EEquine strongyles are harmful gastrointestinal parasites affecting horses’ health and productivity. In tropical regions, environmental conditions, including temperature and soil type, significantly influence the development and survivability of strongyle larvae. This study aims to assess the development and survival of third-stage larvae (L3) of strongyles under different temperatures and soil types commonly found in Malaysia. Faecal samples from five adult horses aged between 22–24 years that were kept under a semi-intensive management system and had no history of recent anthelmintic treatment for the past six months and did faecal culture at various controlled temperatures: 21 ± 1°C, 26 ± 1°C, 29 ± 1°C and 32 ± 1°C, and soil type (peat, clay, residual and sandy). The presence of strongyle eggs was identified using faecal floatation, while larval development was monitored daily for 30 consecutive days using the Baermann technique and light microscopy. The time required for development from egg to L3 was shortest at 29°C–32°C (5–6 days) and longest at 21°C–26°C (8–9 days). Peat soil supported the highest survivability (up to 68%) compared to sandy and clay soils, which had the lowest survivability (50% and 41%, respectively). This study highlights the role of tropical soil environments in larval survival. It offers insights into improved parasite control strategies, suggesting future investigations using field trials to explore the role of faecal moisture and microbial interactions in L3 persistence.